System oceny działalności spółek zależnych na przykładzie amerykańskiej korporacji - Gubicz, Dorota (The Activity Estimation System in Subsidiary Companies Based on an American Corporation, 2005)
This short information shows the structure of internal control in international companies. Finance control and audits according to Sarbanes - Oxley Act and Corporate Governance. Companies intro-duce a new system, which assist in meeting the compliance requirements of the Sarbanes - Oxley Act. This Act requires: document internal controls, asses adequacy of controls, tests effectiveness of con-trols, certify the control environment is effective for accurate financial reporting.(original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1085, s. 192-200